2008
DOI: 10.2193/2007-014
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Shorebird Response to Trail Use Around San Francisco Bay

Abstract: We studied how human use of trails affected foraging shorebirds over 24 months at 3 locations around San Francisco Bay, California, USA. By observing sites with trails and nearby sites without trails, we assessed whether numbers of trail users had an effect on the number of birds, species richness, or proportion of shorebirds foraging on tidal mudflats. Human use at non‐trail sites averaged <1 person/hour, whereas use at trail sites averaged 68 people/hour. Despite these differences, we found no negative effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Damage to subtidal communities may be more severe in soft muds than in firm sands (Eckrich and Holmquist 2000). Hikers, swimmers, and bird-watchers sometimes (but not always) reduce populations of birds in the shore zone (van der Zande and Vos 1984;Cardoni et al 2008;Trulio and Sokale 2008). Likewise, off-road vehicles kill beach vegetation, crush animals (Schlacher et al 2008a, b), and compact sediments.…”
Section: Recreational Activitiesmentioning
confidence: 99%
“…Damage to subtidal communities may be more severe in soft muds than in firm sands (Eckrich and Holmquist 2000). Hikers, swimmers, and bird-watchers sometimes (but not always) reduce populations of birds in the shore zone (van der Zande and Vos 1984;Cardoni et al 2008;Trulio and Sokale 2008). Likewise, off-road vehicles kill beach vegetation, crush animals (Schlacher et al 2008a, b), and compact sediments.…”
Section: Recreational Activitiesmentioning
confidence: 99%
“…Birds that remain in areas with high disturbance may spend less time roosting and more time being vigilant or active (Barbee 1994, Morton 1996. Results from studies of disturbance effects on foraging behavior have been inconsistent with some studies finding a negative association between human activity and time spent foraging Gochfeld 1991, Thomas et al 2003), whereas others found no effect (Barbee 1994, Morton 1996, Trulio and Sokale 2008. We were interested in testing disturbance effects on migratory shorebird abundance and activity, as well as in determining whether disturbance influenced distribution of shorebirds across ocean beach microhabitat zones between the dune line and swash zone.…”
mentioning
confidence: 99%
“…Although observational studies are convenient and inexpensive, their results are often difficult to interpret because effects of disturbance are potentially confounded by variations in environmental or habitat factors unrelated to disturbance , Gutzwiller 1991, Hill et al 1997, Sutherland 2007, Neuman et al 2008. This is especially problematic for studies of migrating shorebirds because their behavior and local abundance are sensitive to many factors, such as weather, time of day, tide levels, prey densities, and predation risk, that are highly dynamic in coastal environments and are often confounded (Burger et al 1977, Peters and Otis 2005, Beauchamp 2006, Yasue 2006, Trulio and Sokale 2008. Gutzwiller (1991) and others advocated use of experimental studies, especially ones that compare control and treatment areas or before and after disturbance measures, because of their ability to isolate disturbance effects and demonstrate causal relationships (Walters and Holling 1990, Gutzwiller 1991, Hill et al 1997, Sutherland 2007.…”
mentioning
confidence: 99%
“…We found that humans have the greatest impact on birds in the study areas. The results from studies of disturbance effects on foraging behavior have been inconsistent with some studies found a negative association between human activity and time spent foraging (Burger & Gochfeld 1991;Thomas et al 2003), whereas others found no effect (Barbee 1994;Morton 1996;Trulio & Sokale 2008). Previous studies have demonstrated that human activity on beaches affects shorebird feeding activities (Burton 2007;Thomas et al 2003).…”
Section: Resultsmentioning
confidence: 99%